I don't know where I went wrong, but it's interesting for me. Please check where my fault is! It is obvious that the below equation is correct:

$$\frac{3dx}{3x}=\frac{5dx}{5x}$$ $$u=3x$$and$$v=5x$$ $$\frac{du}{u}=\frac{dv}{v}$$ integrate both sides: $$ln(u)=ln(v)$$ $$u=v$$ $$3x=5x$$ so, $$3=5$$

  • 11
    $\begingroup$ When you integrate both sides you need your constant of integration. "+C" $\endgroup$
    – Doug M
    Aug 10, 2018 at 20:25
  • 2
    $\begingroup$ Forgot the constant of integration $\endgroup$ Aug 10, 2018 at 20:25
  • 29
    $\begingroup$ An excellent example of the importance of remembering the constant of integration. I will certainly use this as an example when I teach integration .... $\endgroup$
    – Mandelbrot
    Aug 10, 2018 at 20:27
  • 15
    $\begingroup$ 3 does equal 5. ... plus a constant. $\endgroup$
    – fleablood
    Aug 10, 2018 at 20:28
  • 18
    $\begingroup$ @fleablood In this case multiplied by a constant. $\endgroup$ Aug 10, 2018 at 21:32

3 Answers 3


Integrating we obtain

$$\ln(u)=\ln(v)+ C$$

  • 1
    $\begingroup$ Where $C = \ln u - \ln v = \ln \frac{u}{v}$ So, $\ln u = \ln \left(v \cdot \frac{u}{v}\right)$, giving us $3 = 5 \cdot \frac{3}{5}$..Spelling out what you were implying. $\endgroup$
    – Davislor
    Aug 11, 2018 at 1:16
  • 3
    $\begingroup$ @Davislor I'm not implying nothing! I just gave the answer to the OP that is "I don't know where I went wrong". You are free to add your own answer here below with all the details you like. Morover try to be polite when you formulate any kind of request. $\endgroup$
    – user
    Aug 11, 2018 at 6:38
  • $\begingroup$ Sorry to have sounded impolite! I just wanted to acknowledge that you were aware of the steps you left out. $\endgroup$
    – Davislor
    Aug 11, 2018 at 7:22
  • $\begingroup$ @Davislor Thanks for the clarification. I would like to proceed as in the answer here below exponentiating both sides to obtain $u=kv$ wiith $k=e^C=3/5$. Let add your own answer if you like to suggest another way. Bye $\endgroup$
    – user
    Aug 11, 2018 at 7:33

If you're taking an indefinite integral, then you need to include constants. Integrating, we get $\ln(u)+C_1 = ln(v)+C_2$. We can collect $C_1$ and $C_2$ into one constant by setting $C_3 = C_2-C_1$, getting $\ln(u) = ln(v)+C_3$. We can then exponentiate both sides, getting $u=ve^{C_3}$. Setting $C_4=e^{C_3}$, this becomes $u=C_4v$. In this case, $C_4$ is $\frac35$.

If you're taking definite integrals, you need to include the limits. Suppose we integrate starting from $x = 1$. Then $u$ starts at $3$. So when we integrate $\frac{du}u$, we have $\ln(u)$ at the upper limit, but we have to subtract $\ln$ of the lower limit, and the lower limit is $3$. So we have that the definite integral is $\ln(u)-\ln(3)=\ln(\frac u3)$. Similarly, for $v$, we get that the definite integral is $\ln(\frac v 5)$. Plugging in $u=3x$ and $v=5x$, we get $\ln(\frac {3x}3)=\ln(\frac {5x} 5)$, which simplifies to $\ln(x)=\ln(x)$.

  • $\begingroup$ After setting $C_3$, the LHS is just $ln(u)$ $\endgroup$
    – CDspace
    Aug 10, 2018 at 21:33

To turn my comment into an answer, your proof is correct up to the step $$ \frac{\mathrm{d} u}{u} = \frac{\mathrm{d} v}{v} $$

At that point, as others have said, you forget to add the constants of integration when you integrate:

$$ \ln u + \mathrm{C_1} = \ln v + \mathrm{C_2} $$

Substituting $\mathrm{C} = \mathrm{C}_2 - \mathrm{C}_1$ gives us:

$$\begin{align} \ln u &= \ln v + \mathrm{C} \\ \ln u - \ln v &= \mathrm{C} \\ \end{align}$$

Substituting for $\mathrm{C}$ in the first equation just gets us $\ln u = \ln u$, which is clearly no contradiction. A little more interesting, perhaps, is to turn our identity for $\mathrm{C}$, $\ln u - \ln v$, into $\ln \frac{u}{v}$ and then substitute that into the other equation above to get:

$$\begin{align} \ln u &= \ln v + \ln \frac{u}{v} \\ &= \ln \left( v \cdot \frac{u}{v} \right) \end{align}$$

Now take the exponential of both sides.

$$\begin{align} u &= v \cdot \frac{u}{v} \\ 3x &= 5x \cdot \frac{3x}{5x} \\ 3 &= 5 \cdot \frac{3}{5} \end{align}$$

This is presumably what Serge Seredenko meant when he said in his comment that 3 is equal to 5, “[i]n this case multiplied by a constant.”


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.